Legal Liability, Institutional Environment and Audit Pricing: Insights from China’s Securities Law Revision - Zhang, Lu; Bin Balia, Sophee Sulong (International Journal of Economics and Financial Issues, 2024)
This study investigates the impact of China's revised Securities Law (2019) on the audit pricing strategies of A-share listed companies. Using a Difference-in-Differences (DID) approach and a sample of 26,057 firm-year observations from 2016 to 2022, we find that the new law led to a significant increase in audit fees, especially for non-state-owned enterprises and firms in regions with stronger legal institutions. We attribute these effects to the heightened legal liability and regulatory scrutiny faced by auditors under the new regime, which incentivizes them to enhance audit quality and charge higher risk premiums. Our results are robust to a series of sensitivity tests and alternative specifications. We conclude that the revised Securities Law has achieved its intended objectives of improving market transparency and investor protection but at the cost of higher compliance burdens for listed companies. Our findings have important implications for policymakers, regulators, and market participants in China and other emerging economies undergoing similar legal and institutional reforms.